Linking larval nutrition to adult reproductive traits in the European corn borer Ostrinia nubilalis. (21st September 2015) - Bonoan, Rachael E.; Al‐Wathiqui, Nooria; Lewis, Sara
Abstract: Throughout an organism's lifetime, resources are strategically allocated to many different functions, including reproduction. Reproduction can be costly for both sexes; females produce nutrient‐rich eggs, whereas males of many species produce large and complex ejaculates. In capital breeding insects, nutrients are mainly acquired during the larval period, yet allocation decisions impact the reproductive fitness of adults. The present study examines the effect of larval dietary nitrogen on both male and female reproductive traits in the European corn borer moth Ostrinia nubilalis Hübner, whose adults do not feed and whose males transfer a large, nitrogen‐rich spermatophore. One day post‐eclosion, O. nubilalis adults reared on one of three different diets (3.0%, 1.6%, or 1.1% nitrogen) are mated and two experiments are undertaken: one to measure nitrogen and carbon content of male ejaculates, and the other to determine female fecundity and fertility. Although male larval diet does not alter the percentage nitrogen content of adult somatic tissue, males reared on the higher nitrogen diet (3.0%) produce spermatophores with increased nitrogen relative to somatic nitrogen. Furthermore, females raised on the 3.0% nitrogen diet receive spermatophores with lower carbon : nitrogen ratios and thus more nitrogen. Overall, females lay more eggs as their larval dietary nitrogen increases, although they lay fewer eggs when their mates are raised on the higher (3.0%) nitrogen diet. This suggests that O. nubilalis females may use male‐derived nitrogen not to supplement egg production, but rather for somatic maintenance. Overall, the present study furthers our understanding of how larval diet can affect adult fitness in Lepidoptera.